PENGARUH PROMOSI, MOTIVASI BELANJA HEDONIS DAN PENGARUH EXPERIENTIAL MARKETING TERHADAP MINAT KUNJUNG ULANG KONSUMEN CAFÉ SILOL JOGJA - Dewi Sianipar; Daniel Joel Immanuel Kairupan (LPPM STIE YKPN Yogyakarta, 2023)
The purpose of this research is to analyze Experiential marketing, to the interest of visitors to SiLOL Jogja cafe. This research is quantitative research whose source of research data is primary data obtained from a sample of SiLOL cafe visitors. The data selection technique was carried out using purposive sampling, namely by distributing 117 questionnaires to the respondents. This research method also uses multiple linear regression analysis methods. The results of this study prove that Experiential marketing has a significant effect on the interest of repeat visits to SiLOL Jogja cafe consumers in sense, feel, think, act, and relation, either simultaneously or partially. This promotion is also the variable that has the most influence on the decision to visit SiLOL Jogja, cafe customers.